How the Left Can Win Arguments and Influence People A Tactical Manual for Pragmatic Progressives - Wilson, John K. (NYU Press, 2000)
If we were to rely on what the pundits and politicians tell us, we would have to conclude that America is a deeply conservative nation. Americans, we hear constantly, detest government, demand lower taxes and the end of welfare, and favor the death penalty, prayer in school, and an absolute faith in the free market. And yet Americans believe deeply in progressive ideas. In fact, progressivism has long been a powerful force in the American psyche. Consider that a mere generation ago the struggle for environmentally sound policies, for women's rights, and for racial equality were fringe movements. Today, open opposition to these core ideals would be political suicide. Drawing on this wellspring of American progressivist tradition, John K. Wilson has penned an informal handbook for the pragmatic progressive. Wilson insists that the left must become more savvy in its rhetoric and stop preaching only to the converted. Progressives need to attack the tangible realities of the corporate welfare state, while explicitly acknowledging that "socialism is," as Wilson writes, "deader than Lenin." Rather than attacking a "right-wing conspiracy," Wilson argues that the left needs one, too. Tracing how well-funded conservative pressure groups have wielded their influence and transformed the national agenda, Wilson outlines a similar approach for the left. Along the way, he exposes the faultlines of our poll- and money-driven form of politics, explodes the myth of "the liberal media," and demands that the left explicitly change its image. Irreverent, practical, and urgently argued, How The Left Can Win Arguments and Influence People charts a way to translate progressive ideals into reality and reassert the core principles of the American left on the national stage.